Intersectionality as Critical Social Theory - Hill Collins, Patricia (Book collections on Project MUSE., 2019)
Offers a set of analytical tools for those wishing to develop intersectionality's capability to theorize social inequality in ways that would facilitate social change. While intersectionality helps shed light on contemporary social issues, Collins notes that it has yet to reach its full potential as a critical social theory. She contends that for intersectionality to fully realize its power, its practitioners must critically reflect on its assumptions, epistemologies, and methods. She places intersectionality in dialog with several theoretical traditions (from the Frankfurt school to black feminist thought) to sharpen its definition and foreground its singular critical purchase, thereby providing a capacious interrogation into intersectionality's potential to reshape the world.